1978
DOI: 10.1038/hdy.1978.106
|View full text |Cite
|
Sign up to set email alerts
|

Non-mendelian female sterility in Drosophila melanogaster: influence of ageing and thermic treatments

Abstract: SUMMARYCrosses between certain Drosophila melanogaster strains may give rise to female sterility of non-Mendelian determination. Reduced fertility is observed in Fl females, known as SF females, from crosses between females of " reactive" strains and males of "inducer" strains. The extent of this reduction of fertility depends on the strains which are used in the cross and on two nongenetic factors: age and temperature. The fertility of SF females increases with ageing. Also, exposing them for a short period t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 15 publications
3
40
0
1
Order By: Relevance
“…However, if the TE is inherited from the mother, then the TE remains repressed, and the progeny is fertile ( Fig. 3B; Bucheton 1979;Bingham et al 1982;Rubin et al 1982). Recent studies revealed that derepression of the TE in a dysgenic cross correlates with the absence of cognate piRNAs targeting this element, thereby implicating a failure of piRNA-mediated silencing as a primary reason for element activation (Brennecke et al 2008;Khurana et al 2011;Grentzinger et al 2012).…”
Section: Transgenerational Effects Of Pirnas In Drosophilamentioning
confidence: 99%
“…However, if the TE is inherited from the mother, then the TE remains repressed, and the progeny is fertile ( Fig. 3B; Bucheton 1979;Bingham et al 1982;Rubin et al 1982). Recent studies revealed that derepression of the TE in a dysgenic cross correlates with the absence of cognate piRNAs targeting this element, thereby implicating a failure of piRNA-mediated silencing as a primary reason for element activation (Brennecke et al 2008;Khurana et al 2011;Grentzinger et al 2012).…”
Section: Transgenerational Effects Of Pirnas In Drosophilamentioning
confidence: 99%
“…Previous genetic studies reported that the fertility of SF females can be improved by various aging and thermic treatments applied not only on the SF females themselves but also on their R mothers (Bucheton 1978). The effect of such treatments is maternally inherited but is progressively lost over generations (Bucheton 1979;Bucheton et al 2002;Chambeyron and Bucheton 2005).…”
mentioning
confidence: 99%
“…The effect of such treatments is maternally inherited but is progressively lost over generations (Bucheton 1979;Bucheton et al 2002;Chambeyron and Bucheton 2005). Environmental factors can therefore modify the epigenetic characteristics of R females, as an acquired trait that can be partially transmitted to the progeny.…”
mentioning
confidence: 99%
“…The kinetics of appearance of this new piRNA production is not clear, but some functional evidence has been provided from previous studies concerning the repression capacity inheritance of the I-factor and of the P-element (Kidwell et al 1977;Bucheton 1978;Engels 1979). In both systems, it appears that establishment of repressive capacities, following paternal inheritance of I-or P-elements carrying genomes in a cytoplasm devoid of I-or P-homologous piRNAs, is progressive and require several generations to be completed (Engels 1979(Engels , 1989Bregliano et al 1980;Finnegan 1989;Rio 2002).…”
Section: Discussionmentioning
confidence: 99%